Competing for Market Shares: Why the Order of Moves Matters Even When It Shouldn't - Rudi Stracke; Tanja Hörtnagl; Rudolf Kerschbamer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper analyzes a contest for market shares where two homogeneous firms compete by investing either simultaneously or sequentially. Standard theory predicts that equilibrium investments and payoffs are independent of the order of moves. To test this prediction, we implement two treatments in the lab, one where firms chose investments simultaneously, and one where they invest sequentially. Our results suggest that it is an inherent advantage to move second rather than first even in the absence of strategic concerns. This is so because first movers face strategic uncertainty, while second movers have the power to ultimately determine relative payoffs through their investment choices. This power is particularly valuable in our experiments, since many first movers try to establish a collusive outcome and second movers not only care about own monetary earnings, but also about relative standing vis-à-vis the first mover.
Keywords: D47; L13; L22; 330